Analisa Imbangan Air Irigasi di Lahan Persawahan Kecamatan Metro Timur Kota Metro - Martini, RA. Sri; Revisdah, Revisdah; Agusri, Erny; Jonizar, Jonizar; Fatturrohman, Fatturrohman (Bearing : Jurnal Penelitian dan Kajian Teknik Sipil, 2025)
East Metro District is one of the regions in Metro City where the majority of residents depend on farming for their livelihood. A significant challenge faced by farmers in this area is the lack of sufficient water for rice field irrigation. This study utilizes two methods: the KP-01 manual technique to estimate irrigation water demand and the FJ Mock method to assess water availability. After both values were calculated, a comparison was made to evaluate the balance between water demand and supply. The findings revealed that during Planting Period I, the average irrigation water demand was 0.41 m³/sec, while the available water was only 0.12 m³/sec. In Planting Period II, the average water requirement increased to 0.40 m³/sec, with water availability at 0.08 m³/sec. During Planting Period III, the irrigation demand averaged 0.20 m³/sec, while the available water was only 0.06 m³/sec.